The Ambition of Ambitious Alignment: A Reflection by a Mid-Career Art Historian - Abdullah, Sarena (Teratak Nuromar & ITBM, 2015)
"Ambitious Alignment~: New Hi1:.'lories of Southeas1 Asian Art"1 h. a research programme funded through Getty Foundation's Connecting Art Hislories initiative for the period 2015-2016, and initiated by the Po\·ver Inslitute Foundation for Art & Visual Culture at the University of Sydney. The idea of the programme was initially mooted and developed through a series of plannir.g meetings in 2012, also supported by the Connecting Art Hislories initiative. The meeting!> involved invesligator'> from Sydney University, the programme's c:teering committee,~ and the programme's regional partners, namely, Tnslitut Teknologi Bandung (ITB) and National Gallery Singapore (NGS). The application for Ambitious Alignment..' was finally approved and granted in 2014 for a period of two yearc;. The success of this grant allowed smaller mobility grants to be awarded to fifteen early career researchers to enable them to conduct their archival research projects based on their proposals that had been approved. A significant portion of the grant was also used to fund invesligators, field experts and research participants to attend series of meetings, workshops and public events in Sydney, Bandung and Singapore in 2015 and 2016.